InAs light-to-heavy hole effective mass ratio determined experimentally from mobility spectrum analysis - Wróbel, Jarosław; Umana-Membreno, Gilberto A.; Boguski, Jacek; Złotnik, Sebastian; Kowalewski, Andrzej; Moszczyński, Paweł; Antoszewski, Jarek; Faraone, Lorenzo; Wróbel, Jerzy (Opto-Electronics Review, 2026)
Careful selection of the physical model of the material for a specific doping and selected operating temperatures is a non-trivial task. In numerical simulations that optimize practical devices such as detectors or lasers architecture, this challenge can be very difficult. However, even for such a well-known material as a 5 µm thick layer of indium arsenide on a semi-insulating gallium arsenide substrate, choosing a realistic set of band structure parameters for valence bands is remarkable. Here, the authors test the applicability range of various models of the valence band geometry, using a series of InAs samples with varying levels of p-type doping. Carefully prepared and pretested the van der Pauw geometry samples have been used for magneto-transport data acquisition in the 20–300 K temperature range and magnetic fields up to ±15 T, combined with a mobility spectra analysis. It was shown that in a degenerate statistic regime, temperature trends of mobility for heavy- and light-holes are uncorrelated. It has also been shown that parameters of the valence band effective masses with warping effect inclusion should be used for selected acceptor dopant levels and range of temperatures.